PELAKSANAAN ANALISIS TINGKAT KEPUASAN PELAYANAN TARUNA/I PIP MAKASSAR - Melinda Melinda; Nurfitriany Fakhri; Kurniati Zainuddin; Muhammad Nur Hidayat Nurdin; Sahril Buchori (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
One of the most essential aspects in determining the quality of service received is the satisfaction of customers. Through this program, partners will be helped to learn about and comprehend the cadets' opinions of the PIP Makassar services that have been rendered. The activity was carried out by providing surveys to 582 PIP Makassar cadets via Google form. The SPSS tool was then used to evaluate the questionnaire responses. Based on the findings of descriptive analysis, it is possible to conclude that PIP Makassar cadets are satisfied with the services provided at PIP Makassar.